Sensory Psychology of Supergrain Bakery: Consumer Perception Beyond Taste - Mehak Billa (International Journal of Nutritions, 2026)
Bakery products remain a cornerstone of diets worldwide, yet wheat-based formulations are increasingly supplemented or replaced as consumers demand healthier, more functional alternatives. Supergrains such as quinoa, amaranth, millet, and cowpea, together with fruit-based flours such as guava flour, have been extensively investigated to enrich wheat-based products and improve their nutritional value. At the same time, the science of sensory psychology has become central to product acceptance, as taste, aroma, texture, and emotional response determines whether consumers embrace or reject a nutritionally enriched product, regardless of its nutritional merit. This review synthesises experimental studies published between 2023 and 2026 on the fortification and reformulation of bakery products with supergrains and functional flours. Substituting wheat with quinoa or amaranth increased the protein, fibre, resistant starch, and mineral content of cakes while maintaining acceptable sensory quality at optimal substitution levels. Composite flours combining pearl millet and cowpea delivered nutritional benefits without compromising flavour. Sourdough fermentation of ancient wheat breads reduced phytate content while enhancing mineral bioavailability, phenolic compounds, antioxidant activity, and sensory perception. Guava flour incorporation increased fibre and bioactive compound content, and consumer studies linked enriched cakes to greater satiety as well as more positive emotional responses. Extrusion processing demonstrated the scale-up potential of seaweed-fortified bakery products, although with trade-offs in expansion and crispiness. Collectively, these findings indicate that the future of bakery innovation lies in the integration of nutritional science, processing technology, and consumer psychology.
Keywords: Bakery innovation; Nutritional enrichment; Sensory psychology; Supergrains